Spontaneous coronary artery dissection in a middle-aged woman with acute anterior myocardial infarction: A case report. Issue 31 (August 2018) - Yang, Xue-Qing; Zhu, Hai-Yan; Wang, Xian; Zhao, Huai-Bing; Zhang, Wei; Xiao, Min; Zhang, Li-Jing
Abstract: Rationale: Spontaneous coronary artery dissection is a highly unusual cause of acute coronary disease. It is a result of a hematoma formation within the outer third of the tunica media, with subsequent expansion leading to compression of the true lumen and resultant myocardial ischemia. Patient concerns: We present a case of a middle-aged woman presenting with chest pain with acute anterior myocardial infarction, who did not reveal any of the cardiovascular risk factors. Finally, when pressed further about her past history, the patient revealed she had been taking oral contraceptives for the past 2 years. Diagnoses: The diagnosis is usually confirmed by coronary angiography, but it has some limitations. If necessary, intravascular ultrasound (IVUS) may help in further examinations to reduce the incidence of erroneous diagnosis or missed diagnosis. Interventions: There is no guiding suggestion for the treatment of SCAD. The main treatment methods are 3 aspects: conservative internal medical treatment, stent implantation, coronary artery bypass grafting. The treatment strategy depends mainly on the patienst' clinical symptoms, the hemodynamic state, and the position and quantity of the dissection. In this case, we used stent implantation treatment originally and then we resorted to medical treatment. Outcomes: After careful review and analysis, coronary arteriography results was able to prove the existence of the spiral shaped dissection. We then resorted to medical treatment and her symptoms were gradually relieved. Lessons: SCAD should be suspected in young to middle-aged women with chest pain symptoms, particularly during the perinatal period or for subjects who use oral contraceptives. Doctors should be able to obtain a detailed past history and analyze coronary angiography results carefully.